The impact of perceval sutureless aortic valve in multiple valve surgery: implications of short- and mid-term outcomes—a propensity score matched study - Shin, Jung-Hoon; Joo, Hyun-Chul; Kim, Jung-Hwan; Lee, Sak; Youn, Young-Nam; Lee, Seung-Hyun (Journal of thoracic disease, 2025)
Sutureless aortic valve replacement (S-AVR) is a surgical alternative to conventional aortic valve replacement (C-AVR), recognized for its efficacy and clinical superiority in the treatment of valvular disease. Its use is gradually increasing not only in single-valve procedures but also in multiple valve surgeries. This study aimed to evaluate our experience with the Perceval S-AVR combined with mitral and tricuspid valve surgery such as multiple valve surgery, focusing on the clinical outcomes and operative time. Between January 2017 and December 2022, 141 patients underwent surgical aortic valve replacement (AVR) using the bioprosthetic aortic valve at our institution. Of them, 42 patients (29.8%) underwent S-AVR with multivalve surgery. After 1:1 propensity score matching, 42 patients were selected as study subjects in each group. The primary endpoints were 30-day and follow-up mortality and major valve-related adverse events, such as structural valve dysfunction, valve thrombus, endocarditis, stroke, re-intervention, and pacemaker implantation. In matched cohort, the mean age 74.3±4.2 and 74.2±6.2 years in C-AVR and S-AVR groups, respectively. The in-hospital mortality rates were 2.4% and 0% (P>0.999), and follow-up mortality rates were 4.8% and 7.1% (P>0.99) in C-AVR and S-AVR groups, respectively. Paravalvular leakage and abnormal pressure acceleration were absent in both the groups, and the incidence of postoperative valve-related adverse events did not vary between the groups. The operation time, including for the mitral valve, tricuspid valve, and arrhythmia surgeries, was significantly shorter in the S-AVR group after matching (mean cardiopulmonary bypass time: 132.52±39.20 115.50±25.70 minutes, P=0.001; mean aortic cross clamp time: 100.90±32.12 80.38±18.81 minutes, P<0.001). S-AVR may be considered a viable option in cases requiring multiple valve surgery, as it can reduce operation time without compromising clinical outcomes.